(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
Designing curriculum and teaching delivery programs that can meet the needs of specialized groups of employers and students is challenging in the best of times. When extra criteria are added, such as making a degree program fully online when also limited with the number of fully qualified faculty due to constrained resources, flexibility is a requirement. This is a case study of one such program development project that saw the design and development of a Master-level program of study in Cybersecurity that was designed at one level of expected faculty resource availability that had to rapidly evolve in a new direction due to significant resource restrictions. Built on a model of maximizing the productivity of a few fully qualified faculty by leveraging less qualified but very capable part-time staff to meet the needs of online delivery of large sections of graduate instruction.